Surgical recovery of fractured dental needle in the pterygomandibular space with the aid of computered tomography in pediatric patient - case report - Rojas-Apaza, Zenaida (2025)
Dental needle fracture during anesthetic placement is a rare complication that can cause significant anxiety for both the patient and their family. Complications may range from mild pain, trismus, and dysphagia to injuries involving nerve or vascular structures. We present a case of dental needle fracture in the pterygomandibular space following an inferior alveolar nerve block in a 3-year-old girl. The needle fracture appears to have resulted from the child’s sudden movement during the administration of the dental anesthesia. The needle fragment was located using cone-beam computed tomography (CBCT), and surgical retrieval was successfully performed 24 hours after the incident under general anesthesia. Dental needle fractures are complications that can generally be prevented with proper precautions. However, it is essential to understand the appropriate actions to take should this rare event occur.